Sequence and regulatory responses of a ribosomal protein gene from the fission yeast Schizosaccharomyces pombe. - Nischt, R (1987)
We have determined the nucleotide sequence and mapped the 5' and 3' termini of a ribosomal protein gene. The gene is transcribed into a RNA molecule of about 770 nt and appears to initiate at multiple sites, as judged by SI nuclease analysis. Gene dosage experiments with a plasmid born gene leads to a proportional increase of the messenger RNA, but not to an overproduction of the protein, suggesting a posttranscriptional control mechanism. However, the heat shock response of this gene indicates that there is also a potential for transcriptional control. Comparison of the 5' flanking region of this gene with the ribosomal protein gene S 6 from Schizosaccharomyces pombe and with ribosomal protein genes from Saccharomyces cerevisiae revealed homologous sequences, which may be involved in the regulation of ribosomal protein genes.